2009
DOI: 10.1021/jp9041606
|View full text |Cite
|
Sign up to set email alerts
|

ORR Activity and Direct Ethanol Fuel Cell Performance of Carbon-Supported Pt−M (M = Fe, Co, and Cr) Alloys Prepared by Polyol Reduction Method

Abstract: A polyol reduction method is employed to prepare carbon-supported Pt and Pt-M (M ) Fe, Co, and Cr) alloy catalysts by simultaneous reduction and decomposition of metal precursors with 1,2-hexadecanediol in the presence of nonanoic acid and nonylamine protecting agents. The prepared materials are characterized by powder XRD, HRTEM, and EDX. The face-centered cubic structure of Pt in the prepared materials is evident from XRD. Good dispersion of Pt and Pt alloy nanoparticles on the carbon support is seen from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…As mentioned by Viswanathan, this will be conducive to oxygen adsorption at low potential and thus promoting the ORR kinetics. 20 …”
Section: Resultsmentioning
confidence: 99%
“…As mentioned by Viswanathan, this will be conducive to oxygen adsorption at low potential and thus promoting the ORR kinetics. 20 …”
Section: Resultsmentioning
confidence: 99%
“…Toda et al [146] reported that oxygen adsorption increases in the case of changing of the electronic structure of Pt induced by a transition metal, and then the O-O bond is weakened. For this purpose, various platinum-based bimetallic catalysts, such as Pt-Ni [147,148], Pt-Co [149,150], Pt-Fe [151,152], Pt-Cr [153,154], Pt-Cu [155,156], Pt-V [157,158], Pt-Mn [159], Pt-Bi [35], Pt-Te [160] have been reported. It can be clearly emphasized that modified-platinum catalysts display 1.5-3 times higher catalytic activity than that of pure platinum catalyst.…”
Section: Orr Activity On Various Carbon Supported Nanoparticles Prepamentioning
confidence: 99%
“…Indeed, this peak is centered at 0.70 V vs. RHE on Pd/C-ETEK; 0.72 V vs. RHE on Pd/C-CH2O, 0.74 V vs. RHE on Pd/C-NaBH4 and 0.74 V vs. RHE on Pd/C-EG. Rao et al [152] reported Pt and Pt-M (M: Fe, Co, Cr) alloy catalysts prepared by the polyol method in 1,2-hexadecanediol in the presence of nonanoic acid and nonylamine as protecting agents. The results of linear sweep voltammetry indicated that the Pt alloy catalysts exhibited 1.5-1.7 times higher oxygen reduction activity than that of the as-synthesized and commercial Pt catalyst.…”
Section: Orr Activity On Various Carbon Supported Nanoparticles Prepamentioning
confidence: 99%
“…Well-defined hydrogen desorption and adsorption peaks in the potential range of -0.05 to +0.3 V, and irreversible pre-oxidation and reduction peaks in the potential range of +0.5 to +1.0 V were observed. The electrochemically active surface area (EAS) was determined by assuming that a monolayer of adsorbed hydrogen requires 210 μC/cm 2 for its oxidation [12]. The EAS was then calculated using the following equation [13].…”
Section: Introductionmentioning
confidence: 99%